Massive Open Online Social Learning Environment For English Elearning System varo Martino Mantilla Herrera - Rinatovna Eremeeva, Guzel (2017)
In language learning there is a need for collaborative and social learning. A kind of learning that gives the students the opportunity to work together online and use the foreign languages in real time. This article is to list the kinds of social and learning properties that we already have online. We will give a small review about a new idea MOOSLE (Massive Open Online Social Learning Environment), which uses the collaboration and social environment to build a platform for sharing courses and learning materials. MOOSLE opens a new way for collaboration and gives the users the power of sharing their work and courses and tracking it inside or outside of the system for free. They search for other courses, engage in new MOOCs (massive open online course), work in groups. We are trying to push the reusability to the extreme with MOOSLE, to use the common social properties in a structural collaboration way for learning.